Enhancing Students’ Problem-Solving Ability through STEM-Integrated 5E Learning in the Context of Light Pollution - Utami, Kharisma Arum; Ramli, Murni (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2026)
Problem-solving ability is an essential competency that students need to develop in order to address complex real world issues, including environmental problems. One emerging environmental issue that has received limited attention in school learning is light pollution, which results from excessive artificial lighting and can disrupt ecological balance. Integrating this phenomenon into science learning can provide a meaningful context for developing students’ problem-solving ability. Therefore, this study aims to analyze the effect of Science Technology Engineering and Mathematics (STEM) integrated 5E learning on students’ problem-solving ability in the context of light pollution. This study employed a quasi-experimental method with a pretest–posttest non-equivalent control group design. The participants were Phase E students at a public senior high school in Indonesia. Two classes were selected through cluster random sampling as the experimental and control groups. Data were collected using problem-solving ability tests, observation sheets, and student response questionnaires. Data were analyzed using appropriate non-parametric statistical tests and effect size calculation. The results showed a statistically significant improvement in students’ problem-solving ability in the experimental group, with a moderate effect size. The experimental class also demonstrated higher learning gains compared to the control class. In addition, students responded positively to the learning activities, indicating improved understanding of environmental issues and enhanced creative problem-solving. In conclusion, STEM-integrated 5E learning is an effective approach for improving students’ problem-solving ability while fostering awareness of environmental issues. This approach also highlights the potential of integrating real-world environmental contexts into science education to support more meaningful and relevant learning experiences.